Out of the closet: Lesbian and gay adult educators and sexual orientation issues in the university learning environment - Elizabeth J. Tussled; Edward W. Taylor (Adult Education Research Conference, 1995)
This qualitative study examined how "out" lesbian and gay faculty members deal with sexual orientation in the classroom and how they perceive their own sexual orientation affects the learning environment in adult higher education contexts.